Оценка токсикологического действия СОЖ, используемых при резании металлов - Данилович, В. С.; Шапорова, Е. В.; Яцкевич, О. К. (БНТУ, 2020)
In this paper we consider the problem of the impact of waste lubricating technological means (LTT) on the human body. Particular attention is paid to the main paths of receipt of hazardous substances into the body LTT workers and has the effect of occupational diseases. It is proved that under the influence of oil on the body develop diseases such as lung cancer, throat, lips, men and women - lung cancer, colon, breast and genital organs.